1997
DOI: 10.1108/03090599710161801
|View full text |Cite
|
Sign up to set email alerts
|

The management of training in multinational corporations: comparative case studies

Abstract: Discusses the similarities and differences in the ways in which the training and development function is managed in multinational corporations (MNCs). Presents a comparative analysis (at three levels: international, industry and enterprise, with emphasis on enterprise) of enterprise‐based training in the UK and Australia, set in the context of the food and drink industry; and some of the government policies that affect the industry. Includes case studies of MNCs that operate in both countries, giving details o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In his comparative study of MNCs in the UK and Australia, Noble (1997) found that the MNCs under investigation had evolved an approach to the organisation and management of training that suited their complex stru c t u res. The MNCs in his study allowed cons ide rable auto no my to the ir subsidi aries in develo ping and implementing training and development strategies.…”
Section: Global or Local: The Evidencementioning
confidence: 99%
“…In his comparative study of MNCs in the UK and Australia, Noble (1997) found that the MNCs under investigation had evolved an approach to the organisation and management of training that suited their complex stru c t u res. The MNCs in his study allowed cons ide rable auto no my to the ir subsidi aries in develo ping and implementing training and development strategies.…”
Section: Global or Local: The Evidencementioning
confidence: 99%
“…A comparative study of MNCs in the UK and Australia found that MNCs had developed an approach to the organisation and management of training that best suited their complex structures (Noble 1997). The MNCs allowed substantial autonomy to their subsidiaries in the development and implementation of their T&D practices.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…This is especially the case in the arena of MD, because it is typically seen as a way of exerting control or inculcating cultural expectations (Kamoche, 2000) and building internationally skilled high-potential managers (Scullion & Starkey, 2000). Second, it has been established that there is a tendency for MNE subsidiaries to adopt parent or ''best practice'' norms, particularly in more macro-HRD practices such as training needs analysis, MD delivery and evaluation procedures, while allowing their subsidiaries considerably greater autonomy in the local implementation of training (Noble, 1997;Tregaskis, Heraty, & Morley, 2001). Third, it is well known that the economies of scale associated with MNEs permit access to a richer vein of resources for MD than is possible for many domestic companies.…”
Section: The Effects Of International Strategymentioning
confidence: 99%